2003
DOI: 10.1002/arch.10120
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a putative Bombyx mori TFIIB‐related factor (BRF)

Abstract: To identify the protein domains responsible for its conserved and specialized functions, putative TFIIB-Related Factor (BRF) from the silkworm (Bombyx mori) was compared with BRFs from other organisms. The Bombyx BRF coding region was assembled from three separate and overlapping cDNA fragments. Fragments encoding the middle portion and the 3' end were discovered in the Bombyx mori Genome Project "Silkbase" collection through sequence homology with human BRF1, and the fragment encoding the N-terminus was isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Although this Bdp1-binding block contains low sequence homology, secondary-structure analysis indicates consensus ␣-helical secondary structures in this region. Furthermore, this Bdp1-binding block contains the amino acid sequence Gly328-Glu329-Gln330-Glu331-Leu332 (GEXEL), which was previously reported to be a conserved short motif in Brf1c (25). The structural region of Bdp1 that interacts with this sequence block remains to be determined.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although this Bdp1-binding block contains low sequence homology, secondary-structure analysis indicates consensus ␣-helical secondary structures in this region. Furthermore, this Bdp1-binding block contains the amino acid sequence Gly328-Glu329-Gln330-Glu331-Leu332 (GEXEL), which was previously reported to be a conserved short motif in Brf1c (25). The structural region of Bdp1 that interacts with this sequence block remains to be determined.…”
Section: Discussionmentioning
confidence: 98%
“…Yeast Brf1c (aa 287 to 596) contains three homologous sequence blocks, I (aa 287 to 304), II (aa 461 to 515), and III (aa 570 to 596) (Fig. 1A), that are conserved in S. cerevisiae, Schizosaccharomyces pombe, Candida albicans, Kluyveromyces lactis, and Homo sapiens (22,25). Brf1c exists mostly as a scaffold that holds together the three TFIIIB subunits (12, 26).…”
mentioning
confidence: 99%
“…We believe that TBP and not TRF is involved as the component of TFIIIB in RNA pol III transcription in B. mori and the presence of TRF could be exclusive to Drosophila . The recent characterization of the cDNA encoding Brf1 from B. mori [42] has revealed that individual domains of Brf had considerable similarity to the Drosophila counterpart (55%). However, the domain II, which interacts with TBP in most cases but with TRF in Drososphila , was divergent in B. mori .…”
Section: Discussionmentioning
confidence: 99%